Gifts, Sovereignty and Power: The British and French Trading Companies in Mughal India, 1735-65 - Robert Ivermee (Revue Française de Civilisation Britannique)
This article focuses on the gifts awarded by Indian powers to the British and French trading companies and their representatives in Mughal India in exchange for services rendered – notably the provision of military support. As the Mughal Empire disintegrated, Indian powers solicited the military backing of the British and French to secure their positions of power. When this support was delivered, the companies and their agents were handsomely rewarded with payments and gifts, the awarding of which was part of the performance of sovereignty by the rulers concerned. Beneath this appearance of sovereignty, however, real world power was increasingly vested in the British and French companies, which, confident of their military superiority, exercised more and more control over the rulers that they claimed to serve. What role did the gifts offered by Indian rulers to their European collaborators play in these changing power relations? What do the gifts reveal about how these relations changed? Can a distinction be maintained between gifts and payments? And can objects obtained coercively really be considered gifts? These questions are explored in relation to the political ascent of the British and French companies in the Carnatic and Bengal between 1735 and 1765.